Career Decisions and Dilemmas of Senior High School Students in Disadvantaged Schools: Towards the Development of A Proposed Career Guid-ance Program - Puebla, Joan N. (Future Science / FSH-PH Publications, 2022)
Choosing a career path is one of the most significant decision an individual will make. This quantitative research utilizing both comparative and correlational approaches aimed to assess and describe the career decisions and dilemmas of senior high school students in disadvantaged schools. Respondents in this study were 831 Grade 11 students from four schools who shared a common characteristic. Results show that respondents are aware of the need to make career decisions, there are significant differences between the assessment of the respondents in terms of awareness on the need to make career decisions when grouped according to age and sex. In terms of career decision-making, the respondents have high perceptions; there are significant differences between the assessment of the respondents in terms of their perception on career decision-making when grouped according to age and sex: there is a significant relationship between the respondents' awareness of the need to make career decisions and their career decision-making. And a career guidance program is essential to guide students on their career decisions. The respondents are also aware on the dilemmas they are facing in terms of decision-making. Career decision making has a well-defined influence on a student's future. Thus, parents and the career guidance counselor should continue informing and guiding the students about the significance of choosing a career path.